Transcriptomic profiling reveals connection to lung autonomic nervous system dysfunction and inflammation in pulmonary artery hypertension rats. (3rd October 2022) - Tan, T T; Chen, J; Zhang, Y J; Chen, Y Y; Zhou, Q; Bao, M W; Zhu, W J
Abstract: Background: Pulmonary arterial hypertension (PAH) is a progressive disorder characterized by elevated pulmonary artery pressure, right ventricular failure, and premature death. Previous studies showed autonomic nervous system (ANS) such as sympathetic nerve overactivity or impaired parasympathetic activity was implicated in the pathogenesis of PAH. However, PA remodeling and molecular mechanisms involved in ANS in PAH remain unclear. Purpose: To unravel transcriptional regulation, underlying genes and signaling pathways linking to ANS in PAH. Methods: Publicly available two RNA sequencing (RNAseq) datasets and one single-cell RNA sequencing (scRNAseq) data of lung from rats with PAH induced by high-dose monocrotaline (MCT) were downloaded and reprocessed. For RNA-seq data, STAR and RSEM were used for read alignment and gene expression qualification. Differential expression genes (DEGs) were identified using DSEseq2, after which enrichment analyses were implemented by clusterProfiler. scRNAseq data were analyzed using Seurat. Results: Two RNAseq datasets identified a total of 6, 046 and 2, 172 DEGs respectively, including 2, 945 and 1, 228 up-regulated and 3, 101 and 944 down-regulated. Overlapped DEGs genes among datasets were 1, 123 genes. Functional enrichment analysis of downregulated DEGs in one data pointed out many dysregulated pathways related to nerve system, such as nervous system process, neuron projection, integral component of synaptic membrane in MCT-induced PAH rat (Fig. 1a). Both RNAseq datasets supported upregulated DEGs were also involved in pathways related to ANS including humoral immune response and synapse pruning (P<0.001) (Fig. 1a). Intriguingly, all four genes (Trem2, C1qa, C1qb and C1qc) in synapse pruning were progressively upregulated with severe PAH condition (P<0.05) (Fig. 1b, c). And RT-PCR results confirmed the expression level of these four genes were remarkably increased in PAH rats (P<0.0001) (Fig. 1d). These four genes are known marker genes for macrophages from lung and microglial cell from brain. scRNAseq data of lungs demonstrated these four genes were significantly upregulated in alveolar macrophages from MCT-PAH rats (P<0.001) (Fig. 1e). However, the pathogenic mechanisms of these four genes in nerve fibers from lungs underlying PAH have never been studied and would be further explored using histological analysis in this study. Conclusions: Integrated bioinformatic analysis indicated the association of lung nervous system with PAH. Further, we identified four genes implicated in nervous system, previously reported to link to immune system and provide novel insights into the mechanisms underlying relationship between lung ANS and inflammation in the pathogenesis of PAH. The pathogenetic mechanism of these four genes is being further investigated. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The National Natural Science Foundation of Chinathe Nature Science Foundation of Hubei Province